2019
DOI: 10.1002/art.40820
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Symptomatic Knee Osteoarthritis With Histopathologic Features in Subchondral Bone

Abstract: Objective. Subchondral bone and the osteochondral junction are thought to contribute to osteoarthritis (OA) knee pain. We undertook this study to identify osteochondral pathologies specifically associated with symptomatic human knee OA.Methods. Medial tibial plateau samples from 2 groups of subjects (n = 31 per group) were matched for macroscopic chondropathy scores. The symptomatic chondropathy group had undergone total knee replacement for OA knee pain, at which time specimens of the medial tibial plateau we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 46 publications
4
60
0
1
Order By: Relevance
“…To produce animal OA models that represent human pathology more closely, noninvasive models have been developed, including bipedal walking and mechanical joint loading models. The bipedal walking model is induced by obligatory bipedal exercise, and pathogenic changes in this model are consistent with the pathology observed in humans [22]. The mechanical joint loading model is induced through vertically compressive loading on the knee and ankle joints, which shows a pathogenesis similar to human OA [44].…”
Section: Pain In Clinical Oasupporting
confidence: 74%
See 1 more Smart Citation
“…To produce animal OA models that represent human pathology more closely, noninvasive models have been developed, including bipedal walking and mechanical joint loading models. The bipedal walking model is induced by obligatory bipedal exercise, and pathogenic changes in this model are consistent with the pathology observed in humans [22]. The mechanical joint loading model is induced through vertically compressive loading on the knee and ankle joints, which shows a pathogenesis similar to human OA [44].…”
Section: Pain In Clinical Oasupporting
confidence: 74%
“…They often occur before joint degeneration is established, and resolution of knee pain is associated with reduced BML size, suggesting that BMLs may serve as a biomarker for OA structural damage as well as pain [16,21]. In a study of two groups of subjects matched by macroscopic cartilage damage score, the expression of nerve growth factor (NGF) in osteochondral channels and osteoclast densities in subchondral bone were higher in a symptomatic than in an asymptomatic group [22]. These observations suggest that subchondral pathology is associated with symptomatic knee OA, independent of cartilage lesions.…”
Section: Pain In Clinical Oamentioning
confidence: 99%
“…Hence, we conclude that BMLs at weightbearing components are speci cally associated with weight-bearing pain. We previously demonstrated that subchondral bone histopathology characteristic of BMLs, occurring in middle third of medial tibial plateau (an important weight-bearing area), was associated with knee OA pain, not dependent on chondropathy and synovitis [12].…”
Section: Discussionmentioning
confidence: 99%
“…BMLs represent regions of subchondral bone histologically characterized as displaying increased bone turnover and expression of factors that can increase nerve sensitization [5]. We previously showed that nerve growth factor expression within osteochondral channels and subchondral osteoclast density each is associated with knee OA pain [12], and calcitonin gene-related peptide immunoreactive sensory nerves within osteochondral channels are associated with pain in human and rat knee OA [15]. Activation of sensory nerves in subchondral bone might contribute to weight-bearing pain in knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-nerve growth factor antibody treatment A huge effort has been made in the development of therapeutics targeting nerve growth factor (NGF). NGF might be released upon mechanical stimulation or inflammatory mediators from different cell types including osteoclasts, osteocytes, chondrocytes, synovial fibroblasts, and macrophages in pre-clinical OA studies and human OA [100][101][102][103][104][105] . After the first promising clinical tests using anti-NGF antibodies, the FDA stopped ongoing trials owing to reports of serious adverse side effects with fast progression of OA and increased demand for knee replacement surgery.…”
Section: Treatments Addressing Painmentioning
confidence: 99%